Impact of Social Media on Child Prostitution Network in Pontianak City (Case Study of Rumah Aman Kota Pontianak) - abas, Abas; Mukhlis, Mukhlis; Rahmaniah, Syarifah Ema; Marini, Marini; Purnawan, Endar (Universitas Muhammadiyah Ponorogo, 2024)
The misuse of social media for child prostitution in Pontianak City has increased in recent years, this requires mutual attention. This study aims to describe the types of social media used by online prostitutes in interacting and communicating, and then to describe how social media forms child prostitution networks in Pontianak. The data collection methods carried out are observation, interview, documentation, and data analysis, while this study uses a descriptive qualitative research method approach. In this study, the subjects of this study were officers of the Pontianak City Safe House and the agency that revealed the case, namely the KPPAD team. The results of this study show that social media is an alternative for child commercial sex workers in Pontianak. Related to social media, the most widely used social media is MiChat and WhatsApp GB, besides that social media such as Facebook is also used but not the main one. Furthermore, the results of the study also show that the function of social media is divided into two, namely social media is access to involvement of children in prostitution cases, second social media can form new networks in child prostitution. From the two results of the study, it can be concluded that social media has formed online child prostitution through child online prostitution networks, namely these networks can be formed anytime, anywhere, and by anyone. In addition, as long as social media are labelled as media providers of prostitution services still exist and are easy to download, then social media can form or regenerate new networks.